Association between a nucleotide polymorphism in the calpain 10 gene and carbohydrate metabolism disturbances in patients with polycystic ovary syndrome - Szydlarska, Dorota; Machaj, Małgorzata (Family Medicine & Primary Care Review, 2016)
Polycystic ovary syndrome (PCO S) is a heterogeneous disease entity affecting a significant percentage of women of childbearing age. Despite of the prevalence of this endocrinopathy, the pathogenesis of PCO S is still not fully understood. In recent years, the significant role of insulin in the pathogenesis of PCO S has been emphasized. The coexistence of genetic syndromes of insulin resistance and hyperandrogenism, frequent occurrence of glucose tolerance disorders in women with PCO S and efficacy of the treatment, leading to increased sensitivity to insulin in the treatment of symptoms of PCO S, constitute indirect evidence for the participation of insulin in the pathogenesis of PCO S. Insulin resistance may be present in both lean and obese women with PCO S, and thus it is not directly related to body mass. As a result of years of intensive scientific work aimed at identifying the gene, it has been established that in the study population, a relationship between several polymorphisms (SNPs, single nucleotide polymorphisms) of the calpain 10 gene, a representative of a large family of cytoplasmic proteases, and development of carbohydrate metabolism disorders, including diabetes, exists. The risk of developing type 2 diabetes is not associated with a variant of a single polymorphism of the gene, but rather results from the haplotypes created by alleles of three SNPs, which have been numbered 19, 43, 63. This paper is a summary of recent reports on the presence of the relationship between a single nucleotide polymorphism of the calpain gene and the development of glucose metabolism disturbances in patients with polycystic ovary syndrome. The importance of the calpain 10 gene in the pathogenesis of type 2 diabetes seems vary in different populations and ethnic groups and is likely to be the subject of numerous further studies in the coming years.